Dynamic mechanical analysis of Dwimatrix Biopolymer from waste oil blended with thermoplastic; LDPE/HDPE - M. Rus, A .Z.; M. Salim, N. S. (2021)
This paper presents results from an experimental study on the dynamic mechanical and viscoelastic properties of Biopolymer (BP) from Waste vegetable oils (WVO) blended with two types of thermoplastic polyethylene (PE) which are Low Density Polyethylene (LDPE) and High Density Polyethylene (HDPE). BP blended containing 10–30wt.% of BP were injection moulded. MDI were used as crosslinker agent for modifying the matrices. Dynamic mechanical analysis (DMA) of the blended were performed over a temperature range of 30–120°C for BL and 30-140°C for BH under frequency of 1 Hz. DMA revealed no noticeable changes in a-transition temperature when the BP content was increased or were added. The BP blended revealed better temperature resistance at higher BP content. However, the increase in storage modulus was negligible at BL10 and BH20; due to the agglomeration of the BP. The results of the damping ratio analysis revealed that higher interfacial bonding was achieved by addition of MDI crosslinker agent.